Civil Procedural Execution, a pending subject of justice, of yesterday, of today, but ¿also of tomorrow? (Acta Judicial Journal, 2024)
Enforcement is the pending debt of our civil process, which has traditionally resulted in slow and heavy justice, which is currently speeded up by the hand of electronic administration and digital justice, and which allows us to look to the future of the hand of artificial intelligence and the automation of processes as a system for improving organizational models, which after the consequent reflection and adaptation will allow the fourth industrial revolution 4.0 to make it true that justice is "agile and technologically advanced".
Keywords: Civil procedural execution Monitorio, electronic administration, interoperability, artificial intelligence, procedural automation.